Synthesis of multilayered titanium carbon nitride coatings on stainless steel using a magnetized sheet plasma source - Rosario, Leo Mendel Dilag; Ramos, Henry J. (Quezon City National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
A magnetized sheet plasma source with a magnetron sputtering setup consisting of a pair samarium cobalt (Sm-Co) magnets was utilized for plasma enhanced chemical vapor deposition of multilayered titanium carbon nitride (TiCN) coating on stainless steel substrates. The deposition setup and parameters were optimized and the best carbon source was determined prior to the deposition of multilayered TiCN. The deposition rate of the titanium nitride (TiN) precoating was first optimized by comparing different orientations and configurations of the Sm-Co magnets.
Thesis (Master of Science in Physics)--University of the Philippines Diliman
Keywords: Stainless steel industry